An Unusual Association between Neurofibromatosis Type 1 and Diffuse B Cell Lymphoma - Anas Bizanti; Ariege Bizanti; Ahmad Al-abdouh; Mohammed Mohammed; Maria Pardi (Case Reports in Oncological Medicine)
Neurofibromatosis type 1 (NF-1) is known to be associated with increased risk of malignancy by at least fourfold. Malignant lymphomas are rare in adults with NF-1. Hereby, we present a 75-year-old male with NF-1 complaining of weakness, nausea, and vomiting associated with abdominal pain. Three months prior to presentation, he had suffered a motor vehicle accident (MVA) resulting in multiple rib fractures that was seen in chest X-ray. For the following three months, he had intermittent chest pain, but it was attributed to the recent rib fracture. During this admission, the severity of chest pain worsened and the associated vomiting inclined further investigation; including CT imaging and bone biopsy, it was revealed to be a rare case of diffuse B cell lymphoma in a patient with NF-1. However, we believe the recent MVA caused an anchoring bias in making a prompt diagnosis. In addition, the appearance of the neurofibroma, resulted in suboptimal physical examination, and hence, there was a delay in reaching the diagnosis. We will discuss here the presentation of this case, to highlight the rare association and to increase awareness of when encountering a challenging diagnosis.